Lower Serum IL-10 Linked to Oral Manifestations in Diabetes Patients - Nur'aeny N; Widiasta A; Novianti Y; Zakiawati D; Pratidina NB; Sufiawati I (Diabetes, Metabolic Syndrome and Obesity, 2025)
Nanan Nur’aeny,1 Ahmedz Widiasta,2 Yessy Novianti,3 Dewi Zakiawati,1 Naninda Berliana Pratidina,4 Irna Sufiawati1 1Oral Medicine Department, Faculty of Dentistry, Universitas Padjadjaran, Bandung, Indonesia; 2Department of Child Health, Faculty of Medicine, Universitas Padjadjaran, Dr Hasan Sadikin Hospital, Bandung, Indonesia; 3Oral Medicine Residency Program, Faculty of Dentistry, Universitas Padjadjaran, Bandung, Indonesia; 4Pediatric Dentistry, Faculty of Dentistry, Universitas Padjadjaran, Bandung, IndonesiaCorrespondence: Nanan Nur’aeny, Oral Medicine Department, Faculty of Dentistry, Universitas Padjadjaran, Jalan Sekeloa Selatan I, Bandung, 40132, Indonesia, Tel +628112183008, Email nanan.nuraeny@unpad.ac.idBackground: Diabetes mellitus (DM) is a chronic disease that remains a global health problem with increasing prevalence, particularly in Indonesia. The presence of oral manifestations in patients with DM is influenced by changes in immune system function. Interleukin-10 (IL-10) is an inflammatory marker implicated in DM. However, no studies have investigated the differences in IL-10 levels between non-DM and DM patients with and without oral manifestations.Objective: This study aimed to compare the serum levels of IL-10 between non-DM and DM patients with and without oral manifestations at Dr. Hasan Sadikin Hospital Bandung.Methodology: This observational study used a cross-sectional design. A total of 88 serum samples that met the inclusion criteria were selected, consisting of 37 (42%) samples from non-DM patients, 35 (39.8%) samples from DM patients with oral manifestations, and 16 (18.2%) samples from DM patients without oral manifestations. Serum levels of IL-10 were measured using an enzyme-linked immunosorbent assay (ELISA) kit.Results: Among the 35 DM patients with oral manifestations, xerostomia was the most common (80%). The mean serum IL-10 level was 0.93 pg/mL in non-DM patients, 0.80 pg/mL in DM patients with oral manifestations, and 1.08 pg/mL in DM patients without oral manifestations. Statistical analysis using the Kruskal–Wallis test showed a p-value of 0.008 (p ≤ 0.05), indicating a significant difference in serum levels of IL-10 between non-DM and DM patients with and without oral manifestations.Conclusion: DM patients with oral manifestations had lower IL-10 serum levels compared to non-DM patients and DM patients without oral manifestations. These findings suggest that monitoring IL-10 levels could help identify diabetic patients at higher risk for oral complications.Keywords: diabetes mellitus, interleukin-10, oral manifestation, serum